'I want to tell the story again': re-telling in selected novels by Jeanette Winterson and Alan Warner - Collett, Jenna Lara (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2011)
This thesis investigates acts of 're-telling' in four selected novels by Jeanette Winterson and Alan Warner.Re-telling, as I have defined it, refers to the re-imagining and re-writing of existing narratives from mythology, fairy tale, and folktale, as well as the re-visioning of scientific discourses and historiography. I argue that this re-telling is representative of a contemporary cultural phenomenon, and is evidence of a postmodern genre that some literary theorists have termed re-visionary fiction. Despite the prevalent re-telling of canonical stories throughout literary history, there is much evidence for the emergence of a specifically contemporary trend of re-visionary literature. Part One of this thesis comprises two chapters which deal with Winterson's Sexing the Cherry (1989) and Weight (2005) respectively. In these chapters, I argue that, although the feminist and historiographic elements of her work are significant, there exist further motivations for Winterson's acts of re-telling in both Sexing the Cherry and Weight. In Chapter One, I analyse Winterson's subversion and re-imagining of historiography, as well as her re-telling of fairy tale, in Sexing the Cherry. Chapter Two provides a discussion of Winterson's re-telling of the myth of Atlas from Greek mythology, in which she draws on the discourses of science, technology, and autobiography, in Weight. Part Two focuses on Warner's first two novels, Morvern Callar (1995) and These Demented Lands (1997). In both novels, Warner re-imagines aspects of Christian, Celtic and pagan mythology in order to debunk the validity of biblical archetypes and narratives in a contemporary working-class setting, as well as to endow his protagonist with goddess-like or mythical sensibilities. Chapter Three deals predominantly with Warner's use of language, which I argue is central to his blending of mythological and contemporary content, while Chapter Four analyses his use of myth in these two novels. This thesis argues that while both Winterson and Warner share many of the aims associated with contemporary re-visionary fiction, their novels also exceed the boundaries of the genre in various ways. Winterson and Warner may, therefore, represent a new class of re-visionary writers, whose aim is not solely to subvert the pre-text but to draw on its generic discourses and thematic conventions in order to demonstrate the generic and discursive possibilities inherent in the act of re-telling.
Keywords: Warner, Alan -- Criticism and interpretation; Winterson, Jeanette, 1959- -- Criticism and interpretation; English fiction -- 20th century -- History and criticism